PENYEDIAAN APLIKASI LAYANAN LOKASI BERBASIS LOCATION BASED SERVICE (LBS) - Asti Widyaningsih; Amir Hamzah; Uning Lestari (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2016)
Submission of information can be done manually (face to face) or by utilizing the technology. The technology is widely used today is the android community. According to the survey gs.statcounter, android users on mobile devices worldwide from July 2014-July 2016 reached 63.43%, while in Indonesia reached 70.8%. This study will use the android technology to create location service application that can use members to manage data location services and can be used by the user to search for data location service has coverage of all categories of location service and regional coverage throughout Indonesia. This study uses data user, the data regions in Indonesia (according to the Ministry of Internal Affairs), location services data, and data maps provided by Google Maps. The method used to collect data that method of literature study, observation, and interviews. Designing the system uses object based design with UML and structured design with DFD.The results of this study is the location service application that consists of an application for admin web based and mobile applications to users and members. Admin is not responsible for the data's location service because member can manage its own location services data. Application can be used to find a location service by displaying some information, contacts, route and distance to the location of the user who searched in one device applications.